Inmigración y Estado de Bienestar en España - Moreno Fuentes, Francisco Javier (Política y Sociedad, 2008)
The position of Spain in the international migration system has substantially changed over the last decade. The settlement of immigrant communities poses a series of important challenges to Spanish society. The social protection schemes included in the welfare state are considerably affected by the social, political, cultural and demographic transformations derived from this phenomenon. On the one hand these schemes must define the way to grant access to their services and benefits to the new residents (definition of the boundaries of entitlement to access the health care system, the social services, the education system or the housing policies). On the other hand, they need to articulate mechanisms to respond to the differential demands of a changing population (in terms of socio-demographic structure, cultural and linguistic profiles, as well as biological characteristics). The welfare regime is also subject to a modification in the social perception of its legitimacy due to the increase of the internal social heterogeneity. In addition to posing a challenge, this phenomenon constitutes in itself a good opportunity to identify the weaker points of the social protection system, a necessary step to reinforce it and to guarantee its future sustainability.